Unpacking the Microfoundations of Sustainability Stakeholder Sensemaking in Global Supply Chains - Kusnanto, Eri; Hadi, A Sigit Pramono (Studia Ekonomika, 2024)
This qualitative literature review explores stakeholder sensemaking in global supply chains, focusing on the microfoundations of sustainability. Sustainability challenges in supply chains are characterized as complex and multifaceted, involving economic, social, and environmental dimensions that often intersect and conflict. Multinational enterprises (MNEs) play a critical role in addressing these challenges, navigating diverse stakeholder expectations and contextual variations across global operations. The review synthesizes insights from previous studies to highlight the role of sensemaking processes at individual and organizational levels in shaping sustainability strategies within global supply chains. Sensemaking acts as a cognitive and social process through which stakeholders interpret and respond to sustainability issues, influencing organizational responses and strategy formulation. Despite its contributions, the review acknowledges limitations in generalizability and the need for empirical validation in diverse contexts. Future research could benefit from longitudinal studies to capture the evolving nature of stakeholder interactions and sensemaking dynamics in sustainability initiatives.